Reliability of 3D Stereophotogrammetry for Measuring Postoperative Facial Swelling - Buitenhuis, Margje B; Klijn, Reinoud J; Rosenberg, Antoine J W P; Speksnijder, Caroline M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This study aimed to determine the reliability of three-dimensional (3D) stereophotogrammetry as a measurement instrument for evaluating soft tissue changes in the head and neck area. Twelve patients received a bilateral sagittal split osteotomy (BSSO). Test and retest 3D photographs were captured within the first three postoperative weeks, and a reference 3D photograph was capture at three months postoperatively. Distance measurements, mean and root mean square of the distance map, and volume differences were obtained. Reliability of these parameters was assessed by intraclass correlation coefficients (ICCs), standard error of measurement (SEM), and smallest detectable change (SDC). All distance measurements had an ICC > 0.91, and the distance map parameters and volume differences showed ICCs > 0.89. The neck region presented the largest SEMs (5.09 mL) and SDC (14.1 mL) for the volume difference. In conclusion, 3D stereophotogrammetry is reliable for distance and volume measurements of soft tissues in patients after a BSSO advancement.
Keywords: bilateral sagittal split osteotomy; reliability; stereophotogrammetry; swelling; three-dimensional; General Medicine; Journal Article